2010
DOI: 10.1073/pnas.1005667107
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming cancer cell resistance to Smac mimetic induced apoptosis by modulating cIAP-2 expression

Abstract: Smac mimetics target cancer cells in a TNFα-dependent manner, partly via proteasome degradation of cellular inhibitor of apoptosis 1 (cIAP1) and cIAP2. Degradation of cIAPs triggers the release of receptor interacting protein kinase (RIPK1) from TNF receptor I (TNFR1) to form a caspase-8 activating complex together with the adaptor protein Fas-associated death domain (FADD). We report here a means through which cancer cells mediate resistance to Smac mimetic/TNFα-induced apoptosis and corresponding strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
107
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 25 publications
11
107
1
Order By: Relevance
“…40,41 In addition to these observations, elevated cIAP2 expression in certain cell lines renders cells resistant to Smac mimetics, suggesting that cIAP2 is the decisive factor for protecting cancer cells from Smac mimetic-induced apoptosis. 22 In this study, we show that a USP11-dependent mechanism selectively and specifically regulates cIAP2 stability independent of cIAP1, which may explain the diverse responses of cancer cells to treatment with Smac mimetics, which are currently being tested in the clinic (Figure 7i). 5,14 In contrast to cIAP1, the cIAP2 degradation rate upon Smac mimetic treatment largely varied between cell lines and correlated with USP11 expression.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…40,41 In addition to these observations, elevated cIAP2 expression in certain cell lines renders cells resistant to Smac mimetics, suggesting that cIAP2 is the decisive factor for protecting cancer cells from Smac mimetic-induced apoptosis. 22 In this study, we show that a USP11-dependent mechanism selectively and specifically regulates cIAP2 stability independent of cIAP1, which may explain the diverse responses of cancer cells to treatment with Smac mimetics, which are currently being tested in the clinic (Figure 7i). 5,14 In contrast to cIAP1, the cIAP2 degradation rate upon Smac mimetic treatment largely varied between cell lines and correlated with USP11 expression.…”
Section: Discussionmentioning
confidence: 66%
“…It has previously been reported that several Smac mimetics can induce cIAP2 expression in certain conditions. 22,33 To test whether BV6 increased cIAP2 expression in our conditions, we stimulated cells with TNFα in the presence or absence of BV6. cIAP2 induction following TNFα treatment was not affected by BV6 treatment, excluding the possibility of BV6 affecting cIAP2 transcriptional levels ( Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-kB-mediated cIAP2 gene expression can provide protection against the lethal effects of TNF, presumably by targeting RIPK1 and NIK for ubiquitylation. 65,66 Surprisingly, cIAP2 that is upregulated in response to SMs is resistant to SM-mediated degradation. This is because SM-mediated degradation of cIAP2 depends on the presence of cIAP1.…”
Section: Ciaps In Tnf-r1 Signallingmentioning
confidence: 99%
“…This is in contrast to findings reported using Smac mimetics, suggesting that such agents may overwhelm/ override normal necroptotic response in TNF-a/Fas-treated cells through interactions with cIAPs. [30][31][32] IAP-mediated inhibition of caspases appears insufficient to alter the nature or extent of PCD once initiated. What then is the purpose of such a system in vivo?…”
Section: Discussionmentioning
confidence: 99%